Neurofilament assembly and function during neuronal development. (February 2015) - Laser-Azogui, Adi; Kornreich, Micha; Malka-Gibor, Eti; Beck, Roy
Abstract : Studies on the assembly of neuronal intermediate filaments (IFs) date back to the early work of Alzheimer. Developing neurons express a series of IF proteins, sequentially, at distinct stages of mammalian cell differentiation. This correlates with altered morphologies during the neuronal development, including axon outgrowth, guidance and conductivity. Importantly, neuronal IFs that fail to properly assemble into a filamentous network are a hallmark of neurodegenerative diseases such as amyotrophic lateral sclerosis, Alzheimer's, and Parkinson's disease. Traditional structural methodologies fail to fully describe neuronal IF assembly, interactions and resulting function due to IFs structural plasticity, particularly in their C-terminal domains. We review here current progress in the field of neuronal-specific IFs, a dominant component affecting the cytoskeletal structure and function of neurons.Current Opinion in Cell Biology 2015, 32 :92–101 This review comes from a themed issue onCell architecture Edited byElly M Hol andSandrine Etienne-Manneville For a complete overview see theIssue and theEditorial Available online 28th January 2015 http://dx.doi.org/10.1016/j.ceb.2015.01.003 0955-0674/© 2015 Elsevier Ltd. All rights reserved.